Expeditious emergency room referral pathway improves patient access to otolaryngology care. Issue 6 (30th November 2017) - Johnson, Jeffrey; Jiang, Zi Yang; Martinez, Daniel; Smith, David; Curtis, Elizabeth; Robinson, David; Alava, Ibrahim
Abstract : Objectives: Historically at a multi‐hospital residency program, there was an unexpected number of non‐urgent consults from the county hospital emergency room (ER) that caused residents to make more trips between hospitals and come closer to violating duty hours. Moreover, there was also a poor follow‐up rate for these patients. An alternate pathway to redirect such consults to the Otorhinolaryngology–Head and Neck Surgery (ORL–HNS) clinic, staffed by an attending physician, was devised. This study illustrates how an undemanding process change can improve access to care, and resident duty hours and satisfaction. Study Design: Quality Improvement Study Methods: The average rate of no‐show appointments and overall number of patients referred from the county hospital ER; a survey of impact on resident workload; and an average number of on‐call resident trips to county hospital were compared in the 12 months before and after implementation of an expedited ER referral pathway. Results: The overall number of patients referred to clinic from ER increased by 35% (123 to 166 patients). The average number of completed visits for patients referred to the ORL‐HNS clinic from the ER increased by 29% (91 to 117 patients). There was no statistically significant change in the no‐show rate of said patients. The average number of overnight resident trips to the county hospital, frequency of resident unpreparedness for routine clinical duty and need to alter schedule to avoid duty hour violations all decreased, while resident satisfaction increased. Conclusions: An undemanding process change in a safety‐net, publicly‐funded, county hospital setting can decrease resident workload and improve satisfaction while possibly improving patient access to specialty clinic care and follow‐up rates for patients. Level of Evidence: clinical outcomes, level IV